Antimicrobial resistance patterns in Streptococcus dysgalactiae in a One Health perspective - Glambek, Marte; Skrede, Steinar; Sivertsen, Audun; Kittang, Bård Reiakvam; Kaci, Alba; Jonassen, Christine Monceyron; Jørgensen, Hannah Joan; , Norwegian Study Group on Streptococcus dysgalactiae; Oppegaard, Oddvar (Frontiers in Microbiology, 2024)
Background: Streptococcus dysgalactiae (SD) is an important pathogen in humans as well as in a broad range of animal species. Escalating rates of antibiotic resistance in SD has been reported in both human and veterinary clinical practice, but the dissemination of resistance determinants has so far never been examined in a One Health Perspective.We wanted to explore the occurrence of zoonotic transmission of SD and the potential for exchange of resistance traits between SD from different host populations.We compared whole genome sequences and phenotypical antimicrobial susceptibility of 407 SD isolates, comprising all isolates obtained from human bloodstream infections in 2018 (n=274) and available isolates associated with animal infections from the years 2018 and 2019 (n=133) in Norway.Results: Antimicrobial resistance genes were detected in 70 (26 %), 9 (25 %) and 2 (2 %) of the isolates derived from humans, companion animals and livestock, respectively. Notably, distinct host associated genotypic resistomes were observed. The erm(A) gene was the dominant cause of erythromycin resistance in human associated isolates, whereas only erm (B) and lsa(C) were identified in SD isolates from animals. Moreover, the tetracycline resistance gene tet(O) was located on different mobile genetic elements in SD from humans and animals.Evidence of niche specialization was also evident in the phylogenetic analysis, as the isolates could be almost perfectly delineated in accordance with host species. Nevertheless, near identical mobile genetic elements were observed in four isolates from different host species including one human, implying potential transmission of antibiotic resistance between different environments.We found a phylogenetic delineation of SD strains in line with host adapted populations and niche specialization. Direct transmission of strains or genetic elements carrying resistance genes between SD from different ecological niches appears to be rare in our geographical region.